2021
DOI: 10.1126/science.abl5163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neurodegenerative diseases on human adult hippocampal neurogenesis

Abstract: Disease and hippocampal dysfunction Impaired function of the brain’s hippocampus can underpin psychiatric symptoms and cognitive impairment. Looking at postmortem brain samples from patients affected by any of several neurodegenerative disorders, Terreros-Roncal et al . investigated whether adult neurogenesis was disrupted (see the Perspective by Gage). Indeed, functions of the neurogenic niche shifted and the cells produced were abnormal in shape and differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(170 citation statements)
references
References 35 publications
5
135
0
Order By: Relevance
“…Adult hippocampal neurogenesis, or the continuous addition of newborn neurons to the hippocampus during adulthood, is a phenomenon observed and extensively studied in rodents, primates, humans, and other animals [ 20 , 22 , 23 , 24 , 25 ]. There is robust evidence, based on radiocarbon cell-birth dating and extensive use of endogenous markers, that human hippocampal neurogenesis occurs throughout the entire lifespan [ 20 , 26 , 27 , 28 , 29 , 30 ], although, this process is more pronounced in the first years of life with a persistent decay during the course of aging. Accumulated evidence has shown that hippocampal neurogenesis plays a critical role in cognitive functions including memory consolidation [ 31 ], pattern separation [ 32 , 33 ], memory clearance [ 34 , 35 ] and cognitive flexibility [ 36 ].…”
Section: Physiological Disruptions Contributing To Chemotherapy-related Cognitive Impairmentmentioning
confidence: 99%
“…Adult hippocampal neurogenesis, or the continuous addition of newborn neurons to the hippocampus during adulthood, is a phenomenon observed and extensively studied in rodents, primates, humans, and other animals [ 20 , 22 , 23 , 24 , 25 ]. There is robust evidence, based on radiocarbon cell-birth dating and extensive use of endogenous markers, that human hippocampal neurogenesis occurs throughout the entire lifespan [ 20 , 26 , 27 , 28 , 29 , 30 ], although, this process is more pronounced in the first years of life with a persistent decay during the course of aging. Accumulated evidence has shown that hippocampal neurogenesis plays a critical role in cognitive functions including memory consolidation [ 31 ], pattern separation [ 32 , 33 ], memory clearance [ 34 , 35 ] and cognitive flexibility [ 36 ].…”
Section: Physiological Disruptions Contributing To Chemotherapy-related Cognitive Impairmentmentioning
confidence: 99%
“…The increasingly recognised role of ghrelin as an important modulator of AHN and memory function [ 75 ] comes at a time when aberrant neurogenesis is firmly implicated in age-related cognitive impairment and neurodegenerative disorders in humans [ 30 , 31 ]. We suggest that the relationship between ghrelin acylation and AHN may be relevant to brain ageing, mood-related disorders, and dementias—warranting further investigation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of new functional neurons from adult NSPCs [ 27 , 28 , 29 , 30 , 31 ] is essential for hippocampal-dependent pattern separation memory, which is the ability to discriminate between very similar contexts [ 32 , 33 ]. A decline in the ability to perform pattern separation is associated with age-related cognitive decline and anxiety-related behaviour, and is therefore of considerable interest to the fields of neuroscience and neurology.…”
Section: Central Actions Of Ghrelinmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the existence of human adult neurogenesis is widely accepted within the scientific community, there is some debate as to its significance [ 50 , 51 , 52 ]. Importantly, in both human and rodents, altered adult neurogenesis seems to be a hallmark of the neurodegenerative diseases [ 53 , 54 ]. Therefore, a better understanding of factors that modulate adult neurogenesis may provide potential therapeutic strategies for preventing and/or improving cognitive decline associated with neurodegenerative diseases.…”
Section: Adult Neurogenesismentioning
confidence: 99%